Accelerated carbonization of waste tire via microwave heating: Carbon anode derived from waste tire for sodium-ion battery - Park, Suah; Lee, Gwanwon; Cho, Gaeun; Lee, Youngtae; Jin, Heewon; Cho, Se Youn; Lee, Sungho; Choi, Dalsu (Elsevier BV, 2025)
Waste tires provoke environmental problems, including harmful emissions from incineration and the ecological harms caused by landfilling, leading to increased interest in sustainable recycling methods for waste tires. In this study, we present an efficient methodology for converting waste tires to produce hard carbon, which can be used as an anode material for sodium-ion batteries (SIBs), a promising alternative to lithium-ion batteries. We specifically employed microwave heating, which offers selective and rapid heating by focusing on the fact that waste tires are mainly composed of carbon black and rubber. While rubber is not responsive to microwaves, the carbon black is highly effective microwave-absorbent. By exploiting this characteristic, microwave irradiation could instantly heat the carbon black within the waste tire and facilitate the carbonization process in only 1 min. When compared to the previously reported studies about waste tire derived carbon materials, which required approximately 24 h of processing time including sulfuric acid treatment and prolonged heat treatment, processing time was significantly reduced. Moreover, the electrochemical performance of SIBs based on the 1-minute microwave carbonization of waste tires demonstrated higher capacity and greater stability, even at high current densities, compared to a previous study that required 24 h of processing time.